2010
DOI: 10.1088/0022-3727/43/3/035406
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic, optical and electrical properties of copper-doped zinc sulfide thin films

Abstract: Thin films of ZnS : Cu nanoparticles were prepared by electron beam evaporation on glass substrates. The Cu content was varied from 0 to 9 at%. XRD examination of the as-prepared films revealed the presence of polycrystalline hexagonal ZnS with preferred orientation depending on the Cu content. As annealing was carried out, grain growth was observed and a new orthorhombic copper sulfate phase emerged. The photocatalytic behaviour of ZnS : Cu was mainly evaluated by measuring the decomposition of methylene blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 33 publications
5
45
1
1
Order By: Relevance
“…The above equation clearly shows that W decreases as the dopant content increases [77]. In addition, penetration depth l, of the light into the solid is given by l = 1/a, in which 'a' is the light absorption coefficient at a given wavelength which decreases with increase in dopant concentration [78]. When the value of W approximates that of l, all the photons absorbed generate electron-hole pairs that are efficiently separated.…”
Section: Photocatalytic Degradation Of Aniline Blue (Ab)mentioning
confidence: 97%
See 1 more Smart Citation
“…The above equation clearly shows that W decreases as the dopant content increases [77]. In addition, penetration depth l, of the light into the solid is given by l = 1/a, in which 'a' is the light absorption coefficient at a given wavelength which decreases with increase in dopant concentration [78]. When the value of W approximates that of l, all the photons absorbed generate electron-hole pairs that are efficiently separated.…”
Section: Photocatalytic Degradation Of Aniline Blue (Ab)mentioning
confidence: 97%
“…According to crystal field theory, the trapped electron/hole will be transferred to surface adsorbed water molecules to restore its energy (Fig. 8), thereby suppressing the recombination of photogenerated electron-hole pairs [78]. Since both the oxidation states are highly unstable, the trapped electron will be transferred to oxygen molecule and trapped hole to surface adsorbed water molecules or to dye molecule.…”
Section: Trapping and Detrapping Of Charge Carriersmentioning
confidence: 99%
“…[36] Cu substituted onto Zn sites should function as acceptors and generate free holes. Cu doping and alloying into both phases of ZnS at low concentrations has been previously explored in thin films [37][38][39][40][41] and nanoparticles, [42,43] particularly for electroluminescent applications and with some reports of p-type character; studies have shown Cu to be sparingly soluble up to about 0.06% in zinc-blende ZnS in equilibrium. [44][45][46] In prior work, we synthesized copper-alloyed…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, various film preparation techniques have been successfully employed to produce Cu-doped ZnS thin films such as spray pyrolysis [19], electron beam evaporation [17], chemical bath deposition [20] by a pH controlled solution synthesis technique [15,21], pulsed laser deposition [18] and thermal reaction process [10] combined with dip coating. Among these film preparation techniques, the sol-gel (a wet chemical route) dip coating has become important in both scientific and industrial fields in only for the last two decades due to its several advantages.…”
Section: Introductionmentioning
confidence: 99%